Binary Metal Oxide Supported on TiO2 Catalysts for Selective Oxidation of Benzene to Phenol Under Microwave Irradiation - Liu, Tong; Hou, Jinhui (Asian Journal of Chemistry, 2015)
This paper studied the liquid phase hydroxylation of benzene to phenol with hydrogen peroxide catalyzed by binary metal oxide catalysts (V-Cu and V-Co) supported on TiO2 at room temperature under microwave irradiation. The catalysts were prepared by the impregnated method and characterized by XRD and BET techniques. It was found that the presence of the second metal can improve the phenol production of the typical V/TiO2 catalyst. TiO2 loaded with V and Cu of 5 and 5 wt %, respectively, offered the highest yield of phenol. Various reaction parameters, such as solvent type, reaction time, amount of catalyst and hydrogen peroxide, were investigated to obtain an optimal reaction conditions for phenol formation under microwave irradiation.